Gambling Advertising and Incidental Marketing Exposure in Soccer Matchday Programmes: A Longitudinal Study - Sharman, Steve; Ferreira, Catia Alexandra; Newall, Philip W. S. (Critical Gambling Studies, 2023)
Gambling is marketed in English soccer across various formats such as TV advertising, social media, pitch side hoardings, and shirt sponsorship. There have been recent reductions in TV advertising brought about by self-regulation, but gambling shirt sponsorship remains frequent, and can lead to a high frequency of incidental marketing exposure on TV. Knowledge is lacking on how gambling advertising frequency and marketing exposure have changed over time in other media, such as in matchday programmes. This study addressed this gap via a content analysis of programmes for 44 teams across 3 periods spanning 18 months (N=132). The number of gambling adverts decreased from 2.3 to 1.3 per-programme, while incidental exposure prevalence stayed constant, at a higher rate of 42.7 incidences per-programme. Teams sponsored by gambling companies had more adverts per-programme than those sponsored by other industries (2.3 versus 1.2), and also had more incidental exposure (58.8 versus 20.2). Incidental exposure to gambling marketing was consistently more prevalent (42.7) per-programme than alcohol (3.2) or safer gambling messages (3.1). Furthermore, across all timepoints, 56.8% of dedicated children’s sections contained incidences of gambling marketing. Researchers and policymakers should consider that sports fans can get exposed to gambling marketing through a number of channels outside of TV advertising. Indirect and incidental exposure to gambling marketing remains high, which can be particularly challenging for those experiencing gambling related harm. All forms of gambling marketing must be considered when making legislative changes.